A facile high-speed vibration milling method to mass production of water-dispersible silicon quantum dots for long-term cell imaging1. Issue 44 (16th May 2015) - Ge, Jiechao; Chen, Pengpeng; Jia, Qingyan; Liu, Weimin; Zhou, Hangyue; Zhou, Bingjiang; Liu, Qingyun; Wang, Pengfei
<x xml:space="preserve">Abstract</x> A facile HSVM method has been developed for mass production of water-dispersible SiQDs for long-term cell imaging.